Clinical Evaluation of the Tolerability and Pharmacokinetics of Azilsartan, a Potent Angiotensin Receptor Blocker, in Healthy Chinese Subjects. Issue 4 (25th September 2019) - Li, Xiaojiao; Liu, Jingrui; Sheng, Changcheng; Chen, Hong; Cui, Dongyang; Chen, Guiling; Zhang, Hong; Zhu, Xiaoxue; Wu, Min; Li, Cuiyun; Shen, Zhenwei; Guo, Yingjie; et al.
Abstract: Azilsartan (AZL), the active metabolite of azilsartan medoxomil, is the newest angiotensin receptor blocker that has been approved for the treatment of hypertension in 2012 in Japan. The present study aimed to evaluate the safety and pharmacokinetic properties of AZL in healthy Chinese subjects. We performed 2 phase 1 studies to investigate the pharmacokinetics and safety of AZL in healthy Chinese adults after a single dose (20 mg or 40 mg) or multiple doses of AZL (40 mg/d for 7 days; Study I) and after a single 40‐mg dose under the fasted and fed conditions (Study II). Noncompartmental analysis and nonlinear mixed‐effects modeling were used to analyze the pharmacokinetic properties of AZL. Twenty‐seven healthy volunteers (14 men and 13 women) aged 20‐32 years were enrolled and completed the study. During single dosing of AZL, the pharmacokinetics of AZL exhibited a linear profile between dosage and area under the concentration‐time curve. There is no AZL accumulation after multiple doses. Food had no effect on the pharmacokinetic characteristics of AZL. AZL concentrations were best fit with a 2‐compartment model, and the typical value of clearance was 1.63 L/h. Body weight had an impact on both the apparent clearance and peripheral volume of distribution. The pharmacokinetic parameters were consistent with previous studies in non‐Chinese subjects. Model‐based simulations indicated that a 45‐kg subject would have approximately double the AZL exposure of a 90‐kg subject. Whether the exposure difference has clinical significance needs to be confirmed in further studies among patients.